Taxa de sobrevida dos implantes dentários de diâmetro reduzido: uma revisão sistemática - Barros, Jose Henrique Lopo (2018)
In the beginning of implantology, the indication of the implants was limited to edentulous patients with good bone quantity. Since then several modifications were made to increase its indications that were guided mainly for the clinical necessity to rehabilitate single unit and partial prosthetic spaces. The implants were subjected to surface treatments, improvement to the titanium alloy and decrease in diameter. This last modification allowed the indication of implants for border cases without the necessity of surgery for bone gain. However, there are several questions related to clinical reliability in narrow implants. Therefore, the purpose of this systematic review was to determine the survival rate of narrow implants (≤3.5mm). It was made a search at electronic database (Pubmed, EMBASE and Cochrane Database of Systematic Reviews) up to September 2016. The inclusion criteria were: articles published in English language, studies that were conducted in human beings, narrow dental implants (≤3,5mm) an at least one year of follow up. The articles were excluded if they had one or more of the following characteristics: studies in animals, cohort studies, case/report series, review articles, insufficient follow up (1 year). An initial electronic search identified 116 studies and the manual searching process identified 16 studies. After the titles and abstracts had been read and all duplicates removed, the full texts of 50 studies were obtained. The articles that did not meet the inclusion criteria were excluded, leaving 31 for data extraction. Twenty-one studies were prospective and 10 were retrospective. The data extraction resulted in 3.659 implants that were installed in 2.152 patients and their diameter varied from 1.8 to 3.5mm. Ninety-eight failures were reported. The survival rate for narrow implants found in this systematic review is 97.3%.